Understanding culture and creativity in urban development: what it means for George Town, Penang? - Khoo, Suet Leng (Penerbit Universiti Kebangsaan Malaysia, 2016)
Culture and creativity are fast emerging as catalysts to spur economic development in urban settings. Many Western cities have leveraged upon culture and cultural industries to revitalize and regenerate their urban spaces following a failure in their industrial base. This trend is also unfolding in Asian cities like George Town where the elements of culture and creativity are currently being earmarked as the city’s engine of economic growth and progress. Against this backdrop, this paper aims to explore and understand the meaning of culture and cultural industries in George Town, especially with the influences of internal and external global forces shaping the city’s urban development. As a city that is undergoing constant social transformations, the element of culture and the types of cultural industries that follow suit are also in a constant state of flux. Thus, defining and understsanding culture in a continuously morphing city like George Town will assist urban managers and policy-makers towards more informed decisions on how next to leverage upon culture as the city’s main source of endowment.